Mezzanine financing : tools, applications and total performance - Nijs, Luc (The Wiley finance series, 2013)
"An in-depth explanation of mezzanine financeMezzanine finance products, which have grown increasingly popular in recent years, involve a unique and complex form of analysis because of their hybrid nature. Because mezzanine finance involves no collateral, it accentuates legal terms, term sheets, and contracts, in addition to depicting dynamics of both debt and equity. Experienced chairman, lecturer, and professor of investment banking Luc Nijs presents readers with a thorough description of product groups, structuring and pricing, and cultural discrepancies in terms of regulation and application in Mezzanine Financing: Tools, Applications and Total Performance. Nijs analyzes common triumphs and failures encountered in mezzanine financing, and he discusses techniques for risk analysis and risk mitigation. A final study of international capital markets, their products' relevance, attractiveness, and liquidity, and the effects on pure equity/fixed-income risk concludes the book. Conveys a professional's advice through case studies of various regions, industries and contexts Provides the only complete analysis of mezzanine finance as no other books take on the topic as their only subject Details an increasingly popular and globally relevant subject in finance Those seeking a detailed explanation of the complexities within mezzanine financing will encounter a professional account in Nijs's book"--